Traders' Awareness of the Safety Fresh Food of Plant Origin at Lakessi Market, Parepare City, South Sulawesi. - Nur Fadillah; Irmayani Irmayani; Irninthya Nanda Pratami Irwan (Citakonsultindo, 2025)
This study aims to describe the level of awareness of traders on the safety of fresh food of plant origin (PSAT) at Lakessi Market, Parepare City, focusing on the commodity of shallots (Allium ascalonicum L.) and red chili peppers (Capsicum annuum L.) of the importance of food safety for public health and product quality. The research method uses a qualitative descriptive approach through observation, in-depth interviews, and documentation of traders and the Parepare City Food Security Office. The results of the study showed that most merchants assess the feasibility of a product only from visual aspects such as color and texture, without considering the risk of chemical or biological contamination. Prevention efforts are carried out through manual sorting and arranging products on the table so that they do not come into direct contact with the floor, but the condition of the market that is muddy, dusty, and crowded with visitors remains a big challenge. The Food Security Agency has conducted field inspections and laboratory tests on red chili samples, which showed the presence of pesticide residues, although the testing is still qualitative. These findings confirm the need to raise traders' awareness through ongoing education, technical mentoring, and the implementation of post-harvest good practices (GHPs) to ensure the safety of the PSAT. Collaboration between traders and local governments is the key in ensuring safe, healthy, and quality food reaches consumers, while increasing the competitiveness of traditional market products.